2021
DOI: 10.33730/2077-4893.4.2021.252961
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nanoparticles of metals and nonmetals of multicomponent trace element preparation «Avatar-2 protection» and microbial preparation «Azogran» on the incedence and severity of infectious diseases of potato

Abstract: The aim of the research was to study the influence of nanoparticles (NPs) of metals and nonmetals of multicomponent trace element preparation «Avatar-2 protection» and microbial preparation «Azogran» on infectious diseases of potato in vivo. Affection of potato cultivar Suvenir Chernihivskyi by diseases was evaluated in two small plot studies on soddy podzolic soil and alkaline chernozem. Symptoms of common scab and dry rot in tubers were identified visually and then the severity and the rate of the diseases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Recent studies have shown that in the fi ght against viral infections, a promising direction in the fi eld of potato technology is the use of nanotechnology, as well as the combined use of nanoparticles in combination with microbial preparations [4]. Th us, the multi-component microelement preparation «Avatar-2 protection» and the combination of the preparation «Azogran» with the composition of Se+1 nanoparticles signifi cantly reduced the frequency of detection of viral diseases [5].…”
Section: The Influence Of the Complex Bacterial Preparation Azogran O...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that in the fi ght against viral infections, a promising direction in the fi eld of potato technology is the use of nanotechnology, as well as the combined use of nanoparticles in combination with microbial preparations [4]. Th us, the multi-component microelement preparation «Avatar-2 protection» and the combination of the preparation «Azogran» with the composition of Se+1 nanoparticles signifi cantly reduced the frequency of detection of viral diseases [5].…”
Section: The Influence Of the Complex Bacterial Preparation Azogran O...mentioning
confidence: 99%
“…Th e results of our research are consistent with the data obtained by other authors, who proved the eff ectiveness of the use of the microbial preparation Azogran for combating bacterial, fungal, and viral diseases of potatoes, increasing the marketability of tubers and yield. Th e authors believe that the composition of Se+1 nanoparticles and the preparation Azogran positively aff ected the microbiota of the potato rhizosphere and the physiological state of the plants [4,5]. When Azogran is introduced into the root system of vegetable and technical crops, the nitrogen and phosphorus nutrition of plants improves, their growth and development are signifi cantly stimulated, and productivity increases by 18-37% [22].…”
Section: нй пархоменко ік курдишmentioning
confidence: 99%